2014
DOI: 10.3389/fnhum.2014.00835
|View full text |Cite
|
Sign up to set email alerts
|

The modulatory effect of electrical stimulation on the excitability of the corticospinal tract varies according to the type of muscle contraction being performed

Abstract: Afferent input caused by electrical stimulation of a peripheral nerve increases corticospinal excitability during voluntary contractions, indicating that proprioceptive sensory input arriving at the cortex plays a fundamental role in modulating corticospinal excitability. The purpose of this study was to investigate whether the effect of electrical stimulation on the corticospinal excitability varies according to the type of muscle contraction being performed. Motor-evoked potentials (MEPs) were elicited by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…Facilitation of corticospinal excitability by PES has been reported in previous PES studies ( Ridding et al, 2000 , 2001 ; Kaelin-Lang et al, 2002 ; Khaslavskaia et al, 2002 ; McKay et al, 2002 ; Charlton et al, 2003 ; Knash et al, 2003 ; Tinazzi et al, 2005 ; Mang et al, 2010 , 2011 ; Chipchase et al, 2011a , b ; Golaszewski et al, 2012 ; Andrews et al, 2013 ; Saito et al, 2014 ). In particular, our previous study using similar experimental protocols revealed that short-duration PES increased MEP ( Saito et al, 2014 ). The present study revealed that short-duration ppES was more effective for modulation of corticospinal excitability than was short-duration PES.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Facilitation of corticospinal excitability by PES has been reported in previous PES studies ( Ridding et al, 2000 , 2001 ; Kaelin-Lang et al, 2002 ; Khaslavskaia et al, 2002 ; McKay et al, 2002 ; Charlton et al, 2003 ; Knash et al, 2003 ; Tinazzi et al, 2005 ; Mang et al, 2010 , 2011 ; Chipchase et al, 2011a , b ; Golaszewski et al, 2012 ; Andrews et al, 2013 ; Saito et al, 2014 ). In particular, our previous study using similar experimental protocols revealed that short-duration PES increased MEP ( Saito et al, 2014 ). The present study revealed that short-duration ppES was more effective for modulation of corticospinal excitability than was short-duration PES.…”
Section: Discussionsupporting
confidence: 73%
“…Intervals between the stimulus periods and between the stimulus conditions were set to 5 s to minimize the summative effect of electrical stimulation on MEPs. An interval of 60 ms was selected between the last electrical pulse and TMS trigger to minimize the influence of electrical stimulus pulse on MEP and detect the effect of electrical stimulation on MEP with reference to the our previous study ( Saito et al, 2014 ) that an interval of 60 ms between the last electrical pulse and the TMS trigger did not affect the change in MEP induced by a short duration of PES. Ten TMS trials were performed for each ppES or PES condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend was also present for control conditions involving cortical stimulation alone, but less so when the rats received no stimulation or muscle stimulation only in place of PAS. These observations can be apprised given the evidence that single pulses of peripheral electrical stimulation are insufficient to change corticomotor excitability with or without coincident voluntary contraction in humans (Saito et al, 2014), and that higher frequencies are needed for supraspinal effects (Grospretre et al, 2017). These results indicate that the probes themselves had no effects, but that all stimulation interventions involving cortical stimulation induced a trend towards an LTD-like effect.…”
Section: Overall Depressive Trendmentioning
confidence: 84%
“…In addition, the present study demonstrated that the degree of PED at post-1 min after isotonic contraction tasks is greater than that after isometric contraction tasks. A number of studies reported that the level of activity in the motor cortex during isotonic contraction is greater than that during isometric contraction ( Kasai et al, 1997 ; Yahagi et al, 2003 ; Saito et al, 2014 ). Yahagi et al (2003) and Saito et al (2014) used the TMS method to measure MEP amplitudes during isotonic and isometric contraction.…”
Section: Discussionmentioning
confidence: 99%